Keabsahan Wasiat Yang Dibuat Dengan Llsan Oleh Pewaris Pada Kajian Hukum Perdata Dan Hukum Islam - Aulia Muthiah (DE LEGA LATA: JURNAL ILMU HUKUM, 2019)
Testament is often problematic in its implementation because it is usually made orally by the inheritants. Testament made orally usually results in no written evidence. In the death of the testator, the inherintants might not want to fulfill the will of the testator because it will basically reduce the amount of inheritance to be distributed to the inheritants. This research uses normative juridical method, a method that studies the legality of testament using laws, which is the book of Islamic Law Compilation and Civil Code. It aims to know the legality of the testament orally made by testator. The result of the research states that in Islamic law, testament made orally is acknowledged under the requirement that it presents two witnesses during testament process. The two witnesses can be used as evidence; however, it is concerned that the witness might die at the same time with the testator which result in the loss of evidence. In civil code, on the other hand, it is stated that all testaments should be written either using authentic deed or private deed.